Development Bureaucracy in Banjarasri Village, Tanggulangin District, Sidoarjo Regency - Irgi Achmad Fachrezi; Isna Fitria Agustina (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze the Bureaucracy in Development in Banjarasri Village, Tanggulangin District, Sidoarjo Regency. The type of research used is descriptive qualitative. Data collection techniques were carried out through observation, interviews and documentation. The informants used a purposive sampling technique. The data analysis technique was carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results showed that the Bureaucracy in Development in Banjarasri Village, Tanggulangin District, Sidoarjo Regency was not optimal. The village government performs its duties by involving the community in decision making, so that all planned plans can receive support from the village community